Mast cell degranulation and bradykinin-induced angioedema - searching for the missing link - Porebski, Grzegorz; Dziadowiec, Alicja; Rybka, Hubert; Kitel, Radoslaw; Kwitniewski, Mateusz (Frontiers in Immunology, 2024)
Initiation of the bradykinin generation cascade is responsible for the occurrence of attacks in some types of angioedema without wheals. Hereditary angioedema (HAE) due to C1 inhibitor deficiency (HAE-C1-INH) is one such clinical entity. In this paper, we explore the existing evidence that mast cells (MCs) degranulation may contribute to the activation of the kallikrein-kinin system cascade, followed by bradykinin formation and angioedema. We present the multidirectional effects of MCderived heparin and other polyanions on the major components of the kinin-kallikrein system, particularly on the factor XII activation. Although, bradykinin-and histamine-mediated symptoms are distinct clinical phenomena, they share some common features, such as some similar triggers and a predilection to occur at sites where mast cells reside, namely the skin and mucous membranes. In addition, recent observations indicate a high incidence of hypersensitivity reactions associated with MC degranulation in the HAE-C1-INH patient population. However, not all of these can be explained by IgE-dependent mechanisms. Mast cell-related G protein-coupled receptor-X2 (MRGPRX2), which has recently attracted scientific interest, may be involved in the activation of MCs through a different pathway. Therefore, we analysed reviewed MRGPRX2 ligands that HAE-C1-INH patients may be exposed to in their daily lives and that may affect MCs degranulation. We also addressed discussed the known inter-and intra-individual variability in the course of HAE-C1-INH in relation to factors responsible for possible variability in the strength of the response to MRGPRX2 receptor stimulation. The above issues raise several questions for future research. It is not known to what extent a prophylactic or therapeutic intervention targeting the pathways of one mechanism (mast cell degranulation) may affect the other (bradykinin production), or whether the number of mast cells at a specific body site and their reactivity to triggers such as pressure, allergens or MRGPRX2 agonists may influence the occurrence of HAE-C1-INH attacks at that site.